Synthesis, Characterization and Anti-Inflammatory Activity Assessment of New Ibuprofen Analogues Containing Imidazole-4-One Derivatives - Monther Faisel Mahdi (Journal of Global Pharma Technology, 2018)
Ibuprofen suffers from general side effects of NSAIDs, owing to the presence of free carboxylic group. The study was aimed to retard the adverse effects of gastrointestinal origin. New series of imidazol-4-one derivatives of ibuprofen were synthesized 6a-e. The structures of synthesized compounds have been established on the basis of their spectral FT-IR and 1HNMR data. In vivo acute anti-inflammatory effects of the synthesized compounds were evaluated in rats using egg-white induced edema model of inflammation. The tested compounds and the reference drug produced significant reduction of paw edema with respect to the effect of propylene glycol 50% v/v (control group). ). The effect of Ibuprofen and all tested com pounds started at time (120 min.) except (6c) and (6e) started at (60 min.) which indicate fast onset of action. The effect of tested compounds and Ibuprofen continued until the end of experiment. Compounds (6a), (6b) and (6d) produced significantly lower inhibitory effect than Ibuprofen at time (120-240 min.).Although, compound (6c) exhibit significantly higher inhibitory effect than ibuprofen at time (60-240 min.),but compounds (6a, 6b & 6c) show lower effect at time (120-240 min).Keywords: Anti-inflammatory activity, Imidazol-4-one, Rat paw edema, Ibuprofen analogues.